Business model transformation : identifying the challenges of transitioning from pipes to platforms - Ogbechie, Anthony (2018)
Business models illustrate the narrative of how firms create, deliver and capture value. Consistent revision, and if required complete transformation of an organization’s business model is essential if such an organization wishes to remain sustainable and competitive in today’s volatile marketplace. Yet, presented with the knowledge of the immense benefits of transitioning to a new business model (platforms), organizations still stick to their old and redundant traditional models of business (pipes). This paper sought to identify the impediments/barriers of undertaking and implementing successful business model change in organizations. While previous research has examined enablers of business model transformation, there is little study aimed at identifying and establishing an understanding of the challenges that hinder firms from transforming their business models. Drawn from an in-depth single case study of a Nigerian firm, this paper explores the challenges firms are faced with in the process of undertaking business model change. We equally explore how the identified challenges may be mitigated. Findings from empirical data gathered suggest that the barriers to successful business model change are linked to the general complexity associated with the business model concept, structure and culture of the organization and the role of leadership and management know-how in the management of change processes.